Investigation of Microbial Safety and Shelf-life of Locally Produced Bread and Cake in Tangail City, Bangladesh (Journal of Environmental Science and Natural Resources, 2017)
The study was carried out to assess the microbial quality for shelf life of different bread and cake samples, locally produced in Tangail city of Bangladesh. A total 10 samples of different brand bread and cake were collected from different shop kipper for microbiological analysis. The total viable count (TVC) of samples ranged from 1.0 × 102 cfu/g to 1.3 × 106 cfu/g at first day, 1.17 × 108 cfu/g to 7.3 × 1010 cfu/g at third day and 2.35 × 1014 cfu/g to 1.2 ×1018cfu/g at fifth day, where WHO permitted maximum 2.0x105 cfu/g for TVC. Total coliform count (TCC) ranged from 2 cfu/g to 244 cfu/g at first day, 1.07× 105 cfu/g to 3.3× 108 cfu/g at third day and 2.08 × 1010 cfu/g to 1.9 × 1014 cfu/g at fifth day (maximum permitted value 200 cfu/g). Again, total fungal count (TFC) ranged from 6 cfu/g to 1.1 × 106 cfu/g at first day, 1.23× 106 cfu/g to 2.2 × 1012 cfu/g at third day and 1.82× 1013 cfu/g to 9.2 × 1017 cfu/g at fifth day (maximum permitted value 1×105 cfu/g). According to the WHO Standard, the microbiological parameters of all collected bread and cake were out of the permitted standards after third day. It was postulated that lack of good manufacturing practices including poor hygiene and sanitation, nutrient rich bread and cake makes a good medium for microbial growth. Therefore, an immediate step should be taken to aware the bakery owner as well as consumers about the sanitation and hygiene to make safety food products.J. Environ. Sci. & Natural Resources, 10(1): 81-84 2017